Efficiency of Pollution Tolerance Index (PTI) of macroinvertebrates in detecting aquatic pollution in an oxbow lake in India - Ghosh, Dipankar; Department of Ecological Studies, University of Kalyani, Kalyani, Nadia, West Bengal – 741235, India. (2018)
This paper evaluates the efficiency of a macroinvertebrate-based Pollution Tolerance Index (PTI) in detecting aquatic pollution in the Chhariganga oxbow lake in India. In this lake, calculated PTIs were compared with results from an array of physicochemical water and sediment parameters and to a macroinvertebrate diversity assessment conducted in parallel for the same lake. The obtained PTI values fell in a range (between 20 and 31) that are indicative of an absence of organic pollution according to the literature, and are normally reported for systems devoid of anthropogenic activity (for instance no monsoonal polluting jute retting activities). However, in the light of the results for the assessed water and sediment physicochemical parameters, and the support of diversity indexes of macroinvertebrates, using data from the same lake, it was possible to conclude that the obtained PTI values do not reflect the true pollution status of this oxbow lake. As PTI values and diversity indexes contradict each other in detecting pollution, it is advised to take both parameters into consideration when using macroinvertebrates to assess aquatic health.